2009
DOI: 10.5089/9781451873948.001
|View full text |Cite
|
Sign up to set email alerts
|

Financial Sector Surveillance and the IMF

Abstract: The global financial crisis has magnified the role of Financial Sector Surveillance (FSS) in the Fund's activities. This paper surveys the various steps and initiatives through which the Fund has increasingly deepened its involvement in FSS. Overall, this process can be characterized by a preliminary stage and two main phases. The preliminary stage dates back to the 1980s and early 1990s, and was mainly related to the Fund's research and technical assistance activities within the process of monetary and financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…Although the Fund carries out the surveillance task since the time of its creation, its systematic involvement in financial sector surveillance is relatively new because it can be traced back to the 1994 Mexican and 1997–98 Asian financial crises (Gola and Spadafora 2009: 3). Both crises offered a conspicuous example of the implications of weak financial systems and of the speed with which financial vulnerabilities spread across the globe 9.…”
Section: Explaining the Shift To Systemic Supervisionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the Fund carries out the surveillance task since the time of its creation, its systematic involvement in financial sector surveillance is relatively new because it can be traced back to the 1994 Mexican and 1997–98 Asian financial crises (Gola and Spadafora 2009: 3). Both crises offered a conspicuous example of the implications of weak financial systems and of the speed with which financial vulnerabilities spread across the globe 9.…”
Section: Explaining the Shift To Systemic Supervisionmentioning
confidence: 99%
“…This has been done in two steps. First, IMF research showed that the potential connection between financial sector policies and financial crises identifying the major sources of risks (Gola and Spadafora 2009: 10–2). Second, internal studies started connecting financial sector surveillance with a systemic focus.…”
Section: Explaining the Shift To Systemic Supervisionmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes to the Fund's surveillance that led the organization to focus on domestic financial sector policies can be traced back to the period that followed the 1994 Mexican crisis. Although the Fund had already been involved with financial sector surveillance since the 1980s, through the publication of regular reports and analyses, the Mexican crisis provided the catalyst for expanding the scope of that surveillance (Gola and Spadafora, 2009: 3). In particular, the crisis offered a conspicuous example of the implications of weak financial systems and of the speed with which financial vulnerabilities spread across the globe.…”
Section: Organizational Fields and The Configuration Of Policy Changementioning
confidence: 99%
“…In particular, the recognition of the importance of financial sector issues to macroeconomic stability did not find an outright application in IMF surveillance practices because the Fund's long-standing experience and routines for macroeconomic surveillance slowed down the development of financial sector surveillance. For instance, in order to guide IMF staff members’ approaches to financial sector issues, the organization adopted the so-called ‘macroeconomic relevance test’ (Gola and Spadafora, 2009: 45). That is to say, staff members were expected to cover non-core issues such as financial sector issues in their analyses only to ‘the extent to which they actively and directly impinge upon the effective conduct of macroeconomic policy’ (IMF, 1999: 63).…”
Section: Organizational Fields and The Configuration Of Policy Changementioning
confidence: 99%